A First Look at Harm Toward Animals by Bahamians in Childhood - Fielding, William J.; Oenbring, Raymond Austin; Brennen, Shane; Carroll, Marie C.; Bethel, Nicolette; Minnis, Jessica (International Journal of Bahamian Studies, 2011)
This paper reports the first known study on childhood cruelty towards animals in The Bahamas. An internet survey involving 1,558 respondents allowed childhood cruelty, using the Children and Animals Inventory (CAI), to be investigated in the context of other violent behaviours in the child’s home. The homes of children who did no harm animals were less violent than the homes of children who harmed animals. Consistent with other studies, males were more likely to harm animals than females. Males were more likely than females to harm sentient animals. While the use of violence to train children was not associated with a higher CAI score, domestic violence and the presence of a gun in the home were associated with a higher CAI score. The implications of these findings as they relate to the treatment of living creatures are discussed.